Marketing Challenges of Corporate Social Responsibility: Case Study of Mobile Telephone Operators in Ecuador - Bonilla Freire, Janeth; Chabusa Vargas , Jorge; Tello Caicedo, Grace; Cedeño Velasco, Alexander (Revista Universidad de Guayaquil, 2020)
This article integrates Corporate Social Responsibility CSR and marketing by analyzing howthe marketing literature onCSR has been discussed by examining not only definitions as a firstpart. But also. the Marketing Challenges of Corporate Social Responsibility: Case Study ofMobile Telephone Operators in Ecuador. The methodology applied was the documentary andintegral correlational. As a result. this analysis showed that the implementation of CorporateSocial Responsibility Marketing strategies has an important influence on consumers.considering them as partners in the retribution to society through Social Responsibilitymarketing policies and strategies. This is confirmed with the result of the test in SPSS wherethe alternative hypothesisis accepted that the increase in mobile telephone lines was positivelyaccused by the population growth in Ecuador.
Keywords: Marketing; Corporate Social Responsibility; CSR; Strategic Factors; Community